New perspectives in the study of the congenital syphilis: A narrative review / Novas perspectivas no estudo da sífilis congênita: Uma revisão narrativa - Rodriguez, Andrea Tatiana Durán- (2020)
Syphilis is still an infection of public health significance, particularly due to its impact during pregnancy and the possibility of mother-to-child transmission that may occur at any stage of pregnancy. Congenital syphilis can lead to miscarriage, stillbirth, perinatal death, premature birth, and clinical manifestations in the newborn. In prospective, the perinatal morbidity and mortality rates due to congenital syphilis are even greater than those due to HIV infection. Overall, both syphilis and congenital syphilis remain a serious public health issue mainly due to flaws both prenatal care systems and syphilis prevention and control programs. This review discusses vertical transmission of the syphilis agent the Treponema pallidum subsp. pallidum, the clinical manifestations of congenital syphilis, the current guidelines for the evaluation and treatment of infants born to mothers with gestational syphilis, the global epidemiology and ongoing research efforts to better understand the pathogenetic mechanisms employed by the syphilis agent to cross the placental barrier and cause congenital infection.